```Question 422111
Let L = Leah's age, S = Sue's age, and J = John's age

So because "Leah is 6 years older than Sue", we know that L = S+6 (ie add 6 years to Sue's age to get Leah's age)

Since "John is 5 years older than Leah", we also know that J = L+5

Finally, we know that "the total of their ages is 41", which tells us that L + S + J = 41

So simply plug in J = L+5 to get

L + S + (L+5) = 41

L + S + L + 5 = 41

Now plug in L = S + 6 to get

(S+6) + S + (S+6) + 5 = 41

S + 6 + S + S + 6 + 5 = 41

Now let's solve for S

S + 6 + S + S + 6 + 5 = 41

3S + 17 = 41

3S = 41 - 17

3S = 24

S = 24/3

S = 8

So Sue is 8 years old (since S = 8 )

So Leah is L = S+6 = 8+6 = 14 years old (since L = 14)

And John is J = L + 5 = 14 + 5 = 19 years old.

Notice that the sum of their ages is

8+14+19 = 22+19 = 41

If you need more help, email me at <a href="mailto:jim_thompson5910@hotmail.com?Subject=I%20Need%20Algebra%20Help">jim_thompson5910@hotmail.com</a>

Also, please consider visiting my website: <a href="http://www.freewebs.com/jimthompson5910/home.html">http://www.freewebs.com/jimthompson5910/home.html</a> and making a donation. Thank you

Jim
```